ln(3x-8)=ln(x+6)

Simple and best practice solution for ln(3x-8)=ln(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(3x-8)=ln(x+6) equation:


Simplifying
ln(3x + -8) = ln(x + 6)

Reorder the terms:
ln(-8 + 3x) = ln(x + 6)
(-8 * ln + 3x * ln) = ln(x + 6)
(-8ln + 3lnx) = ln(x + 6)

Reorder the terms:
-8ln + 3lnx = ln(6 + x)
-8ln + 3lnx = (6 * ln + x * ln)
-8ln + 3lnx = (6ln + lnx)

Solving
-8ln + 3lnx = 6ln + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-6ln' to each side of the equation.
-8ln + -6ln + 3lnx = 6ln + -6ln + lnx

Combine like terms: -8ln + -6ln = -14ln
-14ln + 3lnx = 6ln + -6ln + lnx

Combine like terms: 6ln + -6ln = 0
-14ln + 3lnx = 0 + lnx
-14ln + 3lnx = lnx

Add '-1lnx' to each side of the equation.
-14ln + 3lnx + -1lnx = lnx + -1lnx

Combine like terms: 3lnx + -1lnx = 2lnx
-14ln + 2lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-14ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), '2ln'.
2ln(-7 + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-7 + x)' equal to zero and attempt to solve: Simplifying -7 + x = 0 Solving -7 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + x = 0 + 7 x = 0 + 7 Combine like terms: 0 + 7 = 7 x = 7 Add '-1x' to each side of the equation. x + -1x = 7 + -1x Combine like terms: x + -1x = 0 0 = 7 + -1x Simplifying 0 = 7 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4.93-9.2v=0.66v | | 5-8h-6= | | 3a-10=x-3 | | -22y=8 | | 6=.5x-3 | | 4y+(3y-44)+y=180 | | (w-4/9)*-2/3=4/5 | | 12=3(3n-5) | | 2d+3d=15 | | (w-4/9*-2/3=4/5 | | 3p^2+10p-4=0 | | Y=0.2(3.8) | | 12/(5-8)-4(-2) | | -5+2+3d-8d= | | -15.3=-7.5k+55.1 | | -2-5i/3i=0 | | 5y^2-108=0 | | 8x-5x=19+11 | | 3500.00(x+20.00)=217000.00 | | 10x^3-4x^2-6x= | | (x+5)*3= | | 4y+(3y+44)+y=180 | | 0.6*(r+0.2)=1.8 | | q=7q | | (4p-4/p)*(9p-9/4p^2) | | 0=-16x^2+32 | | 6.9=89.7y | | 2=(-3x)+5 | | 0.14285714285714290= | | 5(x-3)+6=-4(-2x+6) | | 2y+x+9=98 | | -2x-6+3x= |

Equations solver categories